2022
DOI: 10.1007/s00366-022-01729-z
|View full text |Cite
|
Sign up to set email alerts
|

Sharp phase-field modeling of isotropic solidification with a super efficient spatial resolution

Abstract: The phase-field method provides a powerful framework for microstructure evolution modeling in complex systems, as often required within the framework of integrated computational materials engineering. However, spurious grid friction, pinning and grid anisotropy seriously limit the resolution efficiency and accuracy of these models. The energetic resolution limit is determined by the maximum dimensionless driving force at which reasonable model operation is still ensured. This limit turns out to be on the order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Recall that η (ω) and n (ω) depend on the level-set function ϕ h , see Eqs. (25) and (26). The micro-macro transition for the laminated microstructure is discussed in Appendix A.…”
Section: Laminated Element Technique (Let) For Materials Interfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recall that η (ω) and n (ω) depend on the level-set function ϕ h , see Eqs. (25) and (26). The micro-macro transition for the laminated microstructure is discussed in Appendix A.…”
Section: Laminated Element Technique (Let) For Materials Interfacesmentioning
confidence: 99%
“…Preliminary computations have revealed that the convergence of the Newton method at the global level is severely affected by the non-differentiable functions (the absolute value and Macauley brackets) that are involved in the formula for the volume fraction η (ω) in element ω, see Eq. (25).…”
Section: Finite-element Treatment Of the Let-pf Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…By numerical resolution issues, conventional phase-field models require the diffuse interface width to be chosen at least four times larger than the grid spacing. This limitation can be overcome by advanced discretization techniques [39] or by employing the newly proposed sharp phase-field method, which allows the operation with interface widths on the scale of a single distance between two neighboring grid points [40,41].…”
Section: Introductionmentioning
confidence: 99%